Awareness of the Saudi community toward multiple sclerosis in Al-Madinah Al- Munawarrah, Saudi Arabia - Alnefaie, Zayed; Alamri, Ghudai Hatem; Aljarboua, Ghadi Bassam; Alnakhli, Fatimah Mohammed; Abubaker, Jana Jamil; Alhazmi, Lajeen Faisal; Alsadi, Rajaa M-Measar (International Journal Of Community Medicine And Public Health, 2023)
Background: Multiple sclerosis (MS) is an inflammatory neurodegenerative disease affecting the central nervous system (CNS); pathophysiological concepts revealed that exposure to some infectious agents during childhood and genetics involvement played a role. Data reported that females were more affected by MS than males due to genetic predisposition. Recent epidemiological data indicated a higher prevalence of MS in the Arabian Gulf region, with increasing incidence in the Kingdom of Saudi Arabia (KSA). Knowledge about MS shall aid in better management, diagnosis and treatment. This study aimed to assess the level of awareness about MS among participants in Al Madinah Al Munawarrah, KSA. Methods: This was a cross-sectional non-interventional observational survey questionnaire among 381 participants in Al Madinah. Results: The majority of participants were female aged more than 20 years old and high graded; 66.4% of the participants reported good awareness about MS, and 68% reported that MS impact the central nervous system, causing more illness among females aged between 20-39 years. Regarding the risk factors towards MS, Family history of MS and personal history of autoimmune diseases were on top of the list among the participants in relation to risk factors MS, with 43.3% and 38.1%, respectively. Conclusions: In summary, our study shed light on the lack of knowledge about MS among the adult population in Al Madinah AL Munawarrah, KSA. A better understanding of MS shall contribute towards better diagnosing and management.